2020
DOI: 10.1101/2020.03.12.988899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing the Human Heart Rate Circadian Pacemaker through Widely Available Wearable Devices

Abstract: SummaryThe effects of real-world stimuli and how they vary across individuals remains largely unknown for lack of a continuous real-world circadian marker. Here, we show how an underlying circadian rhythm in heart rate (CRHR) can be extracted from several widely used wearables. Analysis of over 130,000 days of data from medical interns on rotating shifts shows how CRHR dynamics are distinct from those of sleep-wake timing and vary greatly among individuals. Analysis of circadian timekeeping in travelers in 5 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Circadian rhythms have been reported to be an important factor in mental health, alertness and human performance [19], with disruptions causing significant effects on mood, processing speed, and working memory [20], as well as anxiety and depression [21]. Recent research has shown that this rhythm can be quantified with wearable devices [22], thus further pushing for a complete wearable solution.…”
Section: Introductionmentioning
confidence: 99%
“…Circadian rhythms have been reported to be an important factor in mental health, alertness and human performance [19], with disruptions causing significant effects on mood, processing speed, and working memory [20], as well as anxiety and depression [21]. Recent research has shown that this rhythm can be quantified with wearable devices [22], thus further pushing for a complete wearable solution.…”
Section: Introductionmentioning
confidence: 99%